HUBUNGAN ANTARA WORK-LIFE BALANCE DENGAN PSYCHOLOGICAL WELL-BEING PADA DOSEN WANITA DI PERGURUAN TINGGI SALATIGA - Yahaziela Nawita Dirfa; Berta Esti Ari Prasetya (Program Studi S1 Psikologi, 2019)
This research was intended to find the correlation between Work-Life Balance with Psychological Well-Being of woman who worked as lecturer in University at Salatiga. The number of participants in this study were 40 woman lecturers with data retrieval using purposive sampling technique. This research was a quantitative correlation. Measuring instruments used in the study was a Work-Life Balance Scale by Fisher (2009) that adapted by Nazirah Adhania (2007) and Psychological Well-Being Scale by Ryff (1995) that adapted by Engger (2015). Data analysis using Spearman's Rho with SPSS 18.0 for Windows. The results showed a significant positive correlation that r = 0,702 with a significance value of 0.000 (p<0,05), which means with higher Work-Life Balance, the Psychological Well Being will be high. Otherwise, with lower Work-Life Balance, the Psychological Well-Being wil be low.